2000
DOI: 10.1038/sj.onc.1203995
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nuclear Bax/p53 complexes is associated with chemotherapy induced apoptosis

Abstract: Mechanisms by which chemotherapeutic agents induce apoptosis are not completely understood. Current knowledge of the actual pharmacologic e ects of chemotherapy and their biochemical mechanisms are better understood than the downstream events, which initiate the apoptotic cascade. The chemotherapeutic agent cisplatin causes DNA damage and can induce apoptosis in several types of human cancers. We found the formation of previously unreported nuclear complexes between the tumor suppressor protein p53 and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Since LNCaP harbours a functional p53 gene, we found that p53 protein expression was increased with increased TNFa concentrations (5 and 10 ng/ml) in all of the cell lines regardless of Id-1 levels (up to threefold, Figure 2a). Bax has been shown to be a downstream effector of the p53 protein in response to TNFa (Raffo et al, 2000). As shown in Figure 2b, after exposure to TNFa, Bax levels were greatly increased (4 -6-fold) in the controls, but the increment was much lower in the Id-1 transfectants (1.1-3.2-fold).…”
Section: Id-1 Expression Protects Lncap Cells From Tnfa-induced Apoptmentioning
confidence: 85%
“…Since LNCaP harbours a functional p53 gene, we found that p53 protein expression was increased with increased TNFa concentrations (5 and 10 ng/ml) in all of the cell lines regardless of Id-1 levels (up to threefold, Figure 2a). Bax has been shown to be a downstream effector of the p53 protein in response to TNFa (Raffo et al, 2000). As shown in Figure 2b, after exposure to TNFa, Bax levels were greatly increased (4 -6-fold) in the controls, but the increment was much lower in the Id-1 transfectants (1.1-3.2-fold).…”
Section: Id-1 Expression Protects Lncap Cells From Tnfa-induced Apoptmentioning
confidence: 85%
“…[32][33][34] Neutralization of Hsp70 through antisense cDNA transfection resulted in tumor death, independent of p53 status. 35 Mortain-p53 interaction was shown to cause inactivation of both wild-type [19][20][21][22][23] and mutant p53 (Lu et al, data not shown) activities, including the deregulation of apoptosis in cancer cells by mechanisms involving formation of nuclear Bax/p53 complexes 36 and their crosstalk with nuclear chaperone, nucleophosmin. 37 Here, we showed that cancer cells under low stress did not have mortalin-p53 interaction and this was not due to their wild-type p53 status.…”
Section: Resultsmentioning
confidence: 99%
“…Cytosolic and mitochondrial fractions were prepared as described by Deveraux et al (1999). The nuclear extracts were separated following the procedure of Raffo et al (2000). For detection of caspase-7 and 9, the treated cells were lysed in lysis buffer containing 20 mM sodium phosphate (pH 7.4), 150 mM NaCl, 0.1% Triton X-100, and 10% glycerol supplemented with a protease inhibitor cocktail tablet.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%